Evaluasi Program Point of Sale (POS) Sebagai Strategi Peningkatan Kesadaran Akuntabilitas Pajak pada Pelaku Usaha di Pasar Banyuasri: Penelitian - Made Devita Indra Kusuma; Ni Luh Gede Erni Sulindawati; Putu Eka Dianita Marviliati Dewi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to evaluate the effectiveness of the Point of Sale (POS) program as a strategy to increase tax accountability awareness among business actors at Banyuasri Market. The evaluation used the CIPP model (Context, Input, Process, Product) to assess the context, resources, implementation, and outcomes of the program. Data were collected through questionnaires and interviews from 92 business actors who were the research subjects. The results indicate that the POS program successfully improved tax accountability awareness, especially in the context, process, and product aspects, although challenges remain in the resource aspect, such as user training and technical support. These findings highlight the importance of improving resource quality and policy support to optimize the program’s implementation. Recommendations include developing intensive training and enhancing technological infrastructure to support the sustainability of the POS program as a tool for increasing tax awareness in traditional markets.